Design of a Model-based Fractional-Order Controller for Optimal Charging of Batteries. Issue 28 (2018) - Mohajer, Sara; Lanusse, Patrick; Sabatier, Jocelyn; Cois, Olivier
Abstract: this paper proposes a robust closed-loop control strategy for optimal charging of batteries. Model-based design of the charging controller is performed based on a coupled electro-thermal aging battery model. For developing an optimal charging strategy, besides minimization of charging time, prolonging the lifetime of the battery is of great importance. As the first step towards implementing a health-conscious charging controller, trajectory planning is carried out by solving a nonlinear optimization problem. The aim is to obtain optimal charging profiles while minimizing the aging. By linearization of the nonlinear battery model, a large uncertainty is observed in the behavior of the linear battery model under different operating conditions. In order to address this problem, CRONE control methodology is used. CRONE control scheme is a robust non-conservative control methodology that shows to be a good candidate for achieving the control targets for our case of study. Subsequently, the design and parametrization of the controller is explained. The simulation results are provided to prove the effectiveness of the CRONE controller. Simulation tests show that the developed controller meets the design requirements while tracking the reference signals in presence of model uncertainties.